PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH DAN MOTIVASI KERJA TERHADAP KINERJA GURU MELALUI LINGKUNGAN KERJA DI GUGUS 3 MENGANTI GRESIK - jurnalpps pps; Rinda Eva Yenny Utami; Nugroho Mardi Wibowo; Mei Indrawati (Prodi Magister Manajemen Universitas Wijaya Putra, 2020)
The purpose of this study was to describe, find out, and analyze the principal's leadership style and work motivation, on teacher performance and the work environment in Cluster 3 Menganti Gresik. This research is an explanatory research with a quantitative approach. The sample used was 47 respondents. Data analysis using PLS with WarpPLS 6.0 program. The results showed that the work environment, teacher performance, and leadership style of the principal were in very good criteria. Work motivation is in good criteria, the principal's leadership style has a positive and significant effect on the work environment, work motivation has a positive and significant effect on the work environment, school leadership style has significant effect on teacher performance, work motivation has no effect on teacher performance, the work environment significant to teacher performance, the principal's leadership style has significant effect on teacher performance through the work environment, and work motivation has a negative and not significant effect on teacher performance through the work environment in Cluster 3 Menganti Gresik.Keywords: principal leadership style, work motivation, work environment, teacher performance